2022
DOI: 10.1155/2022/8339759
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Transcription Factor Creb3l1 Potential Upregulates Ntrk2 in the Hypertensive Microenvironment to Promote Vascular Smooth Muscle Cell-Neuron Interaction and Prevent Neurons from Ferroptosis: A Bioinformatic Research of scRNA-seq Data

Abstract: Background. There is still a lack of knowledge regarding the association between hypertension and ferroptosis. A single-cell approach was used to study the changes in neuropeptide expression as they might contribute to the mechanisms leading to ferroptosis in a hypertensive microenvironment. Methods. We analyzed 11798 cells from the SHR group and 12589 cells from the WKY group of mouse arterial cells. CellPhoneDB was used for cell communication analysis, and the SCENIC method was used to identify key transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…CREB3L1 has been mostly found to be involved in tumour progression in the nervous system and as well to promote vascular smooth muscle cell-neuron interaction. 46,47 In other studies, CREB3L1 has also been found to play an important role in maintaining the function of vascular integrity and regulation of the blood pressure. 48 However, variations in the expression of CREB3L1 in DVT patients remain to be investigated.…”
Section: Discussionmentioning
confidence: 94%
“…CREB3L1 has been mostly found to be involved in tumour progression in the nervous system and as well to promote vascular smooth muscle cell-neuron interaction. 46,47 In other studies, CREB3L1 has also been found to play an important role in maintaining the function of vascular integrity and regulation of the blood pressure. 48 However, variations in the expression of CREB3L1 in DVT patients remain to be investigated.…”
Section: Discussionmentioning
confidence: 94%
“…Secondly, RcisTarget was used to identify TFs and the genes that they directly regulate. Finally, each formed regulon was scored in each cell using AUCell [ 39 ]. Key TFs for tumor cells of each BC subtype were identified with p < 0.01.…”
Section: Methodsmentioning
confidence: 99%
“…CellPhoneDB was used to analyze cell-cell communication. Single-cell gene expression matrices were calculated as input files to predict ligand-receptor interaction pairs among cells [ 27 , 28 ]. We further screened neuropeptide-associated cluster marker genes from these predicted ligand-receptor pairs, which were then included in the subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%